FROM PROJECTS TO PORTFOLIOS: IMPLEMENTING GOOGLE SITES TO FOSTER AUTONOMOUS LEARNING IN ESP-BASED ACCOUNTING COURSES - Andi Asrifan; Musdalifah Musdalifah; Luis Miguel Oliviera De Barros Cardoso; Akhtem A. Dzhelilov (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
In the digital era of higher education, fostering learner autonomy through technology-enhanced pedagogy has become increasingly important, particularly in English for Specific Purposes (ESP) courses that demand contextualized and self-directed learning. Although e-portfolios have been widely implemented in general language education, their pedagogical role in ESP contexts—especially in English for Accounting—remains underexplored, and empirical evidence linking their use to learner autonomy dimensions is still limited. This study aims to investigate the use of Google Sites–based e-portfolios in promoting autonomous learning among students enrolled in an English for Accounting course at an Indonesian university. Employing a mixed-methods design, data were collected from a questionnaire administered to 35 undergraduate students, complemented by portfolio analysis and qualitative feedback. The quantitative data were analyzed descriptively, while qualitative data were examined through thematic analysis. The findings indicate that frequent use of Google Sites is associated with increased student motivation, improved accounting-related vocabulary, and enhanced reflective learning practices. More importantly, the platform supported key dimensions of learner autonomy, including self-regulation, goal-setting, and learning ownership. Despite minor technical challenges, students reported generally positive learning experiences. This study concludes that Google Sites–based e-portfolios represent an effective pedagogical tool for fostering learner autonomy in ESP instruction and offers practical implications for technology integration in discipline-specific language learning.